Perceived Organizational Support (POS) and Organizational Commitment - Dian Ekowati; Mirza Andini (Universitas Airlangga, 2008)
Human resource is critically important aspect of organizations. The functions and roles of human resource have developed from administrative matter into supporting the organization to run the managerial and strategic processes. Expertise, knowledge, and experience of existing human resources in organizations should be suitable and allocated at the right time and place. By properly manage the human resources, organization would be able to obtain qualified human resources that have high commitment to organization. High commitment to organizations will lead to a higher effort in supporting organizational success. In order to gain employees’ commitment to the organizations, management should put some efforts that ensure all aspects of employees’ commitment are fulfilled. This paper is intended to find the significant influence of perceived organizational support (POS) on the dimensions of employee’s commitment, comprising of the affective commitment, continuance commitment, and normative commitment, and to find which one of those dimensions are dominantly influence by POS. This paper employed 50 respondents that were sampled using convenient random sampling. Result showed that there were significant influences of POS on employee’s commitment either in affective commitment. POS can influence the employees’ organizational commitment in all dimensions. This implies that in order to improve organizational commitment, management should provide appropriate managerial supports and ensure that the supports are in line with employee’s aspirations and needs.